1987
DOI: 10.1099/00221287-133-4-825
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Antibody-Binding Sites by Sequence Analysis of Cloned Pilin Genes from Neisseria Gonorrhoeae

Abstract: Immunological analysis of gonococcal pilin (the protein structural subunit of pili) has demonstrated the existence of cross-reacting and type-specific epitopes. The role in adhesion of the domains represented by these epitopes remains unclear. DNA sequencing of a series of pilinexpressing (pilE) genes from a number of otherwise isogenic pilus antigenic variants combined with previous immunological analysis of the corresponding encoded pilins has allowed us to correlate certain predicted amino acid sequences wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…Clearly there is sufficient variation in one individual such that the inoculum passed to a partner would carry a sufficient number of pilin variants to escape from the vaccinated response. Interestingly, the particular combination of semivariable amino acid residues expressed on FA1090 is very similar to those reported for other Gc strains (8,16,31 ). Thus, it appears that the semivariable portion of pilin has a limited number of amino acid sequence combinations that can be expressed.…”
Section: Var29 ---------N-k------------------------------------------supporting
confidence: 59%
“…Clearly there is sufficient variation in one individual such that the inoculum passed to a partner would carry a sufficient number of pilin variants to escape from the vaccinated response. Interestingly, the particular combination of semivariable amino acid residues expressed on FA1090 is very similar to those reported for other Gc strains (8,16,31 ). Thus, it appears that the semivariable portion of pilin has a limited number of amino acid sequence combinations that can be expressed.…”
Section: Var29 ---------N-k------------------------------------------supporting
confidence: 59%
“…Chromosomal DNA from all gonococci tested reacted with the carboxy-terminal pilin probe, which includes invariant domains around the two Cys codons of the gonococcal pilE gene Perry et al, 19876), and also the codons for the SM2 epitope (residues 118-127).…”
Section: Reaction Of Mab Sm2 With Synthetic Peptidesmentioning
confidence: 99%
“…Analysis of the predicted amino acid sequence of cloned genes has revealed that pili are assembled from a repeating array of a pilin polypeptide subunit which varies in apparent M , in the range 17000-22000 between antigenic variants of a strain Nicolson et al, 19876). Such pilins contain distinct conserved (C) and variable (SV and HV) regions but the variable determinants are immunodominant so that the variant pili show little or no antigenic cross-reactivity (Virji et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminal region of gonococcal pilin is immunorecessive (Schoolnik et al, 1984) and the first 30 or so amino acids are strongly conserved in the N-terminal regions of pilins from gonococci and several other Gram-negative bacteria, including meningococci (Hermondson et al, 1978;Olafson et al, 1985), Pseudomonas aeruginosa (Sastry et al, 1983), Bacteroides nodosus (McKern et al, 1983) and Moraxella nonliquefaciens (Froholm et al, 1977). It is possible that SM 1-nonreactive and SM1-reactive pilins share extensive homology between their Nterminal (conserved) regions but that the former lacks the SM 1-reactive epitope which we have recently localized to the region between amino acid positions 48 and 53 on the mature gonococcal pilin sequence (Nicolson et al, 19876).…”
Section: Discussionmentioning
confidence: 99%